Disruption of Francisella tularensis Schu S4 iglI, iglJ, and pdpC Genes Results in Attenuation for Growth in Human Macrophages and In Vivo Virulence in Mice and Reveals a Unique Phenotype for pdpC - Long, Matthew E. (American Society for Microbiology, 2013)
Francisella tularensis is a facultative intracellular bacterial pathogen and the causative agent of tularemia. After infection of macrophages, the organism escapes from its phagosome and replicates to high density in the cytosol, but the bacterial factors required for these aspects of virulence are incompletely defined. Here, we describe the isolation and characterization of Francisella tularensis subsp. tularensis strain Schu S4 mutants that lack functional iglI, iglJ, or pdpC, three genes of the Francisella pathogenicity island. Our data demonstrate that these mutants were defective for replication in primary human monocyte-derived macrophages and murine J774 cells yet exhibited two distinct phenotypes. The iglI and iglJ mutants were similar to one another, exhibited profound defects in phagosome escape and intracellular growth, and appeared to be trapped in cathepsin D-positive phagolysosomes. Conversely, the pdpC mutant avoided trafficking to lysosomes, phagosome escape was diminished but not ablated, and these organisms replicated in a small subset of infected macrophages. The phenotype of each mutant strain was reversed by trans complementation. In vivo virulence was assessed by intranasal infection of BALB/c mice. The mutants appeared avirulent, as all mice survived infection with 10(8) CFU iglJ- or pdpC-deficient bacteria. Nevertheless, the pdpC mutant disseminated to the liver and spleen before being eliminated, whereas the iglJ mutant did not. Taken together, our data demonstrate that the pathogenicity island genes tested are essential for F. tularensis Schu S4 virulence and further suggest that pdpC may play a unique role in this process, as indicated by its distinct intermediate phenotype.